2018
DOI: 10.1186/s13068-018-1237-2
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of hydrogen-producing bacteria and methanogens within an in situ coal seam

Abstract: BackgroundBiogenic and biogenic-thermogenic coalbed methane (CBM) are important energy reserves for unconventional natural gas. Thus, to investigate biogenic gas formation mechanisms, a series of fresh coal samples from several representative areas of China were analyzed to detect hydrogen-producing bacteria and methanogens in an in situ coal seam. Complete microbial DNA sequences were extracted from enrichment cultures grown on coal using the Miseq high-throughput sequencing technique to study the diversity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 71 publications
4
55
1
Order By: Relevance
“…Methanogenesis is commonly associated with sulfate-poor biodegraded petroleum reservoirs 51 and initial steps of anaerobic utilization of organic matter (fermentation) involve hydrolysis followed by bacterial acetogenesis that converts volatile fatty acids into acetic acid, H 2 and CO 2 52 . Alternatively, H 2 is produced by aromatization of compounds present in the seep oil 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Methanogenesis is commonly associated with sulfate-poor biodegraded petroleum reservoirs 51 and initial steps of anaerobic utilization of organic matter (fermentation) involve hydrolysis followed by bacterial acetogenesis that converts volatile fatty acids into acetic acid, H 2 and CO 2 52 . Alternatively, H 2 is produced by aromatization of compounds present in the seep oil 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the previous studies on indigenous microbial community structures of coal and formation water were focused on biogenic or thermogenic methane-containing coal mines [21, 23, 44, 45]. This study provides direct evidence that there are diverse potential microbial coal degraders and methanogens inhabiting opencast coal mine environment, and microbial communities cultured from the grassland soil covering the coal or surrounding the coal mine can efficiently convert the coal into methane with a maximum yield rate reached 74.67 μmol/g coal, which is quite consistent with the methanogenic rate from lignite in the laboratory [20].…”
Section: Discussionmentioning
confidence: 99%
“…The dominant bacterial phyla include Spirochetes , Firmicutes , Proteobacteria and Bacteroidetes [20]. Furthermore, these dominant bacterial phyla and methanogens have been often detected in both biogenic and non-biogenic coalbed methane fields [21]. We et al reported that the microbial communities in thermogenic gas coal mines exhibited potential for biogenic methanogenesis [22].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, strains of Enterobacter Raoultella and Klebsiella have been associated with H 2 and biogas formation (through the generation of acetate), in bioreactors fed with wastewater or GLYC [38,39,40]. The presence of Enterobacter and Citrobacter in biogas formation has also been reported elsewhere [41,42].…”
Section: Resultsmentioning
confidence: 95%